Democratic Deliberation in Deeply Divided Societies: From Conflict to Common Ground (2014)
Through case-analysis and cross-sectional assessment of eleven countries this collection explores the most deeply divided societies in the world in order to highlight what deliberative democracy looks like in a deeply divided society and to understand the conditions that deliberative democracies could realistically emerge in difficult circumstances. © Respective authors 2014. All rights reserved.